Stressors and Coping Mechanisms among Extended-Stay Motel Residents in Central Florida - Gonzalez Guittar, Stephanie (Qualitative Sociology Review, 2022)
Not having a permanent home means living in a constant state of stress. Though much has been written about homelessness and its stressors, very little research has focused on the experiences of those living in liminal housing, such as extended-stay motels. As affordable housing units dwindle in the US, more individuals and families with children have moved into extended-stay motels. In this study, I explore stressors that low-income families living in extended-stay motels experience, as well as their coping mechanisms. Through semi-structured interviews with 18 families with children living in extended-stay motels in the Central Florida region, consistent financial and emotional stressors were identified among all families. Additionally, gender and the community feel of a motel impacts the magnitude of the stress, as well as the ability to cope. Findings from this study suggest that, although families in motels experience constant environmental stressors, community building among precariously housed families may create an informal safety net for the families and thus, alleviate the financial and emotional crisis.